2018
DOI: 10.1161/circulationaha.118.033943
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Interpretation of the QT Interval

Abstract: BACKGROUND: Long QT syndrome (LQTS) is associated with potentially fatal arrhythmias. Treatment is very effective, but its diagnosis may be challenging. Importantly, different methods are used to assess the QT interval, which makes its recognition difficult. QT experts advocate manual measurements with the tangent or threshold method. However, differences between these methods and their performance in LQTS diagnosis have not been established. We aimed to assess similarities and differences between these 2 meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(107 citation statements)
references
References 38 publications
(56 reference statements)
1
102
0
4
Order By: Relevance
“…The end of the T wave was defined as the intersection point of the tangent on the steepest point of the terminal limb of the T wave and the isoelectric baseline. 14 The Bazett (QTc = QT/(RR 1/2 )), Fridericia (QTc = QT/(RR 1/3 )), Framingham (QTc = QT + 0.154 (1 − RR)), and Hodges (QTc = QT + 1.75 (heart rate [HR] − 60)) formulas were obtained for each evaluation point. QT or QTc interval prolongation was identified when the QT or QTc interval was significantly increased compared with baseline.…”
Section: Measurements Of Ecg Parametersmentioning
confidence: 99%
“…The end of the T wave was defined as the intersection point of the tangent on the steepest point of the terminal limb of the T wave and the isoelectric baseline. 14 The Bazett (QTc = QT/(RR 1/2 )), Fridericia (QTc = QT/(RR 1/3 )), Framingham (QTc = QT + 0.154 (1 − RR)), and Hodges (QTc = QT + 1.75 (heart rate [HR] − 60)) formulas were obtained for each evaluation point. QT or QTc interval prolongation was identified when the QT or QTc interval was significantly increased compared with baseline.…”
Section: Measurements Of Ecg Parametersmentioning
confidence: 99%
“…A U wave is always excluded from QT interval analysis. In a large cohort of genotype‐positive LQTS patients, Vink et al found that both methods have a high diagnostic accuracy, however, the cutoff for the tangent method should be shorter (for proposed cut‐off values by age and sex see Vink et al). An online probability calculator of LQTS is available as an aid in the interpretation of the QT interval (http://www.QTcalculator.org).…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al showed that the relative risk of SCD comparing patients with the longest and shortest QT interval was 1.44 (Zhang et al, 2011). Vink et al proved that manual measurement of QT interval corrected according to Bazett formula has a specificity of 86% and a sensitivity of 85% simultaneously (Vink et al, 2018). QT dispersion is also a widely used ventricular arrhythmia risk marker; it is the difference between the longest and shortest QT intervals in the 12-lead electrocardiogram and can be used to estimate the spatial dispersion of ventricular repolarization.…”
Section: Electrocardiographic Estimation Of the Risk For Ventricular mentioning
confidence: 99%